Transnational media concepts and cases - Mishra, Suman; Kern-Stone, Rebecca (Wiley-Blackwell, 2019)
"Transnational Media: Concepts and Cases provides a clear and engaging overview of media communication from a global and a region-based perspective. Rather than focusing on just complex theories and industry-specific analyses, this unique book offers an inclusive, comparative approach to both journalism and entertainment media--introducing readers to the essential concepts, systems, transnational influences, and power dynamics that shape global media flow. Broad coverage of different media forms from Asia, Africa, the Americas, Europe, and Oceania offers country-based and transnational perspectives while highlighting examples of media trends in television, radio, film, journalism, social media, music, and others. Promoting a balanced, multipolar exploration of transnational media, this innovative book discusses topics such as media concentration, the cultural, political, and economic impact of media, and the primary centers of new and traditional media activities. Chapters organized by geographic region offer instructive pedagogical features--including case studies and essays, and illustrations, maps and charts--that strengthen understanding of distinctive and emerging practices in the production, distribution, and consumption of media products.Explores a wide range of global media topics, infrastructures, cultures, and political-economic climates Written in an engaging, relatable, and easy to understand style Covers major aspects of journalism and various forms of entertainment media Organized by regions of the world to reflect a global perspective Includes newly-written case studies by international scholars from each region Designed for undergraduate and graduate courses in comparative media analysis, international media and communication, and related areas of study"--